2023
DOI: 10.1007/s11250-023-03533-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interrelationships of stakeholders involved in the management of transhumance in southern Benin

Abstract: The management of pastoral mobility is a stakeholder-centered approach for the integration of resource conservation and agricultural development. This management of space and its resources is the responsibility of a group of actors who are responsible for resolving con icts of interest. This study aimed at analyzing the in uence of transhumance stakeholders in the municipality of Djidja in southern Benin thanks to semi-structured interviews, which were conducted with 300 transhumance actors. The Likert scale (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Buckland and Guy (2002) , found that the Chinese goose was relatively small, with mature males weighing on average 4.5 kg and females 4.0 kg. Therefore, the relatively poor diets provided to birds in the different agro-ecological zones are most likely the cause of their body weight which remains lower ( Azalou et al, 2023 ). These results could also be explained by the breeding systems in which these animals evolve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buckland and Guy (2002) , found that the Chinese goose was relatively small, with mature males weighing on average 4.5 kg and females 4.0 kg. Therefore, the relatively poor diets provided to birds in the different agro-ecological zones are most likely the cause of their body weight which remains lower ( Azalou et al, 2023 ). These results could also be explained by the breeding systems in which these animals evolve.…”
Section: Discussionmentioning
confidence: 99%
“…Poultry production progresses each year with improvements due to the development of chicken farming and secondarily to the breeding of turkeys, ducks and guinea fowl. To these different breeding systems, is added that of the domestic goose although that it is still in its beginnings ( Hugo, 1997 ; Hamadani et al, 2017 ) in certain countries around the world such as India and even at Benin ( Azalou et al, 2023 ). Thus, on a global scale, domesticated geese came from2 wild species: 1) the greylag goose ( Anser anser ), an ancestor of many domestic breeds, including today's indigenous geese in Egypt and Europe; and 2) the swan goose ( Anser cygnoides ), an ancestor of the Chinese and some African goose breeds ( Silversides et al, 1988 ; Scherf, 2000 ; Abdel-Kafy et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%